Church courts and the people in seventeenth -century England ecclesiastical justice in peril at Winchester, Worcester and Wells. - THOMSON, ANDREW (UCL PRESS, 2022)
Religion meant far more in early modern England than church on Sundays, a baptism, a funeral or a wedding ceremony. The Church was fully enmeshed in the everyday lives of the people; in particular, their morals and religious observance. The Church imposed comprehensive regulations on its flock, such as sex before marriage, adultery and receiving the sacrament, and it employed an army of informers and bureaucrats, headed by a diocesan chancellor, to enable its courts to enforce the rules. Church courts lay, thus, at the very intersection of Church and people. The courts of the seventeenth century - when 'a cyclonic shattering' produced a 'great overturning of everything in England' - have, surprisingly, had to wait until now for scrutiny. Church Courts and the People in Seventeenth-Century England offers a detailed survey of three dioceses across the whole of the century, examining key aspects such as attendance at court, completion of business and, crucially, the scale of guilt to test the performance of the courts. While the study will capture the interest of lawyers to clergymen, or from local historians to sociologists, its primary appeal will be to researchers in the field of Church history. For students and researchers of the seventeenth century, it provides a full account of court operations, measuring the extent of control, challenging orthodoxies about excommunication, penance and juries, contextualising ecclesiastical justice within major societal issues of the times and, ultimately, presents powerful evidence for a 'church in danger' by the end of the century.